Faktor-Faktor Penentu ERC - Christine Dwikarya Susilawati (Universitas Kristen Maranatha, 2008)
This study examined determinant factors of ERC. The research use firms characteristics as determinant factor of ERC. Firms characteristics included three categories: structure-related variables, performance-related variables and market-related variables. Structure variables examined are firm size, leverege, firm age, owership dispersion and inventory method. Performance variables examined are profitability ratio and liquidity ratio. Market variables examined are industry type, audit type and register status at BEJ. This research use purposive sampling with 360 observation from the firms register at BEI, there are 38 manufacture firms (consumption industry) dan 34 non-manufacture firms (property real estate industry) pooled at period 2000-2005. The result examined show two structure variables (firm size and ownership dispersion) and one market variables (industry type) influence ERC. More linger firm size and more higher ownership dispersion have positive influenced to ERC. And ERC for non-manufacturefirms (property real estate industry) more higher than manufacture firms (consumption industry).Key Words: Firm characteristics, determinants factors, ERC, manufacture firms and non-manufacture firms.